Analysis of Parenting Patterns for Early Childhood with Gadget Addiction - Rifyal Novalia; Titin Kusayang (JOYCED: Journal of Early Childhood Education, 2024)
This study aims to analyze the parenting style of parents towards early childhood with gadget addiction in Kerisik Tuo Village, Kayu Aro. The research method used is qualitative with a case study approach. Data was collected through in-depth interviews with five parents who had early childhood addiction to gadgets, as well as direct observation of parent-child interactions. Data analysis was carried out using thematic analysis techniques. The results of the study showed that the parenting pattern of parents for early childhood with gadget addiction in Kersik Tuo Village, Kayu Aro, tended to vary. Some parents adopt an authoritative approach, trying to limit the time spent on gadgets and provide strict supervision over their children's online activities. Meanwhile, some parents tend to give their children full freedom to use gadgets without adequate supervision. These findings identify the importance of the role of parents in controlling the use of early childhood gadgets and the need for education about the negative impact of gadget addiction on child development. This research is expected to contribute to increasing parents' awareness of the importance of healthy parenting in this digital era.